The Market for CEOs - Peter Cziraki; Dirk Jenter (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We study the market for CEOs of large publicly-traded US firms, analyze new CEOs' prior connections to the hiring firm, and explore how hiring choices are determined. Firms are hiring from a surprisingly small pool of candidates. More than 80% of new CEOs are insiders, defined as current or former employees or board members. Boards are already familiar with more than 90% of new CEOs, as they are either insiders or executives who directors have previously worked with. There are few reallocations of CEOs across firms – firms raid CEOs of other firms in only 3% of cases. Pay differences appear too small to explain these hiring choices. The evidence suggests that firm-specific human capital, asymmetric information, and other frictions have first-order effects on the assignment of CEOs to firms.
Keywords: D22; G34; J23; M12; M51; 330; CEO labor markets; CEO-firm matching; assignment models; CEO turnover; CEO compensation